Classification of tumor subtypes leveraging constriction‐channel based impedance flow cytometry and optical imaging. Issue 11 (11th May 2021) - Jiang, Mei; Wang, Xiaojie; Zhao, Xiaoting; Teng, Yu; Chen, Jian; Wang, Junbo; Yue, Wentao
Abstract: As label‐free biomarkers, electrical properties of single cells have been widely used for cell‐type classification and cell‐status evaluation. However, as intrinsic bioelectrical markers, previously reported membrane capacitance and cytoplasmic resistance (e.g., specific membrane capacitance C specific membrane and cytoplasmic conductivity σ cytoplasm ) of tumor subtypes were derived from tens of single cells, lacking statistical significance due to low cell numbers. In this study, tumor subtypes were constructed based on phenotype (treatment with 4‐methylumbelliferone) or genotype (knockdown of ROCK1) modifications and then aspirated through a constriction‐channel based impedance flow cytometry to characterize single‐cell C specific membrane and σ cytoplasm . Thousands of single tumor cells with phenotype modifications were measured, resulting in significant differences in 1.64 ± 0.43 μF/cm 2 vs. 1.55 ± 0.47 μF/cm 2 of C specific membrane and 0.96 ± 0.37 S/m vs. 1.24 ± 0.47 S/m of σ cytoplasm for 95C cells (792 cells of 95C‐control vs. 1529 cells of 95C‐pheno‐mod); 2.56 ± 0.88 μF/cm 2 vs. 2.33 ± 0.56 μF/cm 2 of C specific membrane and 0.83 ± 0.18 S/m vs. 0.93 ± 0.25 S/m of σ cytoplasm for H1299 cells (962 cells of H1299‐control vs. 637 cells of H1299‐pheno‐mod). Furthermore, thousands of single tumor cells with genotype modifications were measured, resulting in significant differences in 3.82 ± 0.92 vs. 3.18 ± 0.47 μF/cm 2 of C specific membrane and 0.47 ± 0.05 vs. 0.52 ± 0.05 S/m of σ cytoplasm (1100 cells of A549‐control vs. 1100 cells of A549‐geno‐mod). These results indicate that as intrinsic bioelectrical markers, specific membrane capacitance and cytoplasmic conductivity can be used to classify tumor subtypes.